2002
DOI: 10.1002/1099-0682(200210)2002:10<2569::aid-ejic2569>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalysed Allylic Substitution: Stereochemical Aspects and Isolation of IrIII Complexes Related to the Catalytic Cycle

Abstract: Keywords: Iridium / Allyl complexes / NMR spectroscopy / Allylic substitution / Asymmetric catalysis Ir-catalysed allylic alkylations of enantiomerically enriched monosubstituted allylic acetates proceed with up to 87% retention of configuration using P(OPh) 3 as ligand. High regioand enantioselectivity of up to 86% ee in asymmetric allylic alkylations of achiral or racemic substrates is achieved with monodentate phosphorus amidites as ligands. Lithium N-tos-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
88
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(97 citation statements)
references
References 20 publications
8
88
0
1
Order By: Relevance
“…This is interesting due to reports on dimer opening by simple coordination of the double bond rather than via C-Cl activation [1,33]. However, it does not seem surprising since similar reactivities have been observed for reactions with allyl bromo/chloro derivatives [34,35]. With regard to 1 H NMR spectroscopy, the signals of [Ir(allyl)(Cl) 2 (COD)] at room temperature in CD 2 Cl 2 are particularly broad but measurements at À60°C reveal a very defined spectrum and in combination with 2D NMR experiments, two isomers in a ratio of 10:3 (different orientation of the allyl ligand) can be identified ( Fig.…”
Section: Reactions Of the Iridium Precursor And The Substratesmentioning
confidence: 54%
“…This is interesting due to reports on dimer opening by simple coordination of the double bond rather than via C-Cl activation [1,33]. However, it does not seem surprising since similar reactivities have been observed for reactions with allyl bromo/chloro derivatives [34,35]. With regard to 1 H NMR spectroscopy, the signals of [Ir(allyl)(Cl) 2 (COD)] at room temperature in CD 2 Cl 2 are particularly broad but measurements at À60°C reveal a very defined spectrum and in combination with 2D NMR experiments, two isomers in a ratio of 10:3 (different orientation of the allyl ligand) can be identified ( Fig.…”
Section: Reactions Of the Iridium Precursor And The Substratesmentioning
confidence: 54%
“…13 Further studies showed that a catalyst generated from [Ir(COD)Cl] 2 and a chiral phosphoramidite ligand containing a dimethyl amino group14 was more active than that containing the phosphine-oxazoline, but enantioselectivities of allylic alkylation reactions with this second system varied from 4% to 86% ee (eq 5), and those of allylic aminations were 11–13% ee (eq 6). 14,15 …”
Section: Prior Studies On Rhodium- and Iridium-catalyzed Allylic Smentioning
confidence: 99%
“…9,22 This overall stereochemical outcome could result from either two steps occurring by inversion of configuration or by all steps occurring with retention of configuration. Reactions of substrates that discourage additions or eliminations with inversion of configuration with the catalyst derived from [Ir(COD)Cl] 2 and P(OPh) 3 gave low yields of substitution product.…”
Section: Introductionmentioning
confidence: 99%